Implementasi Technological Pedagogical Content Knowledge (TPACK) dalam Meningkatkan Kualitas Pembelajaran di SDN 01 Kendawangan - Riyadhul Jannah; Dian Hidayati; Muhammad Zuhaery (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to analyze the implementation of Technological Pedagogical Content Knowledge (TPACK) in enhancing learning quality at SDN 01 Kendawangan as a contribution to achieving Sustainable Development Goal 4 (SDG 4: Quality Education). A qualitative case study approach was employed involving one principal and three classroom teachers representing lower and upper grades. Data were collected through classroom observations, semi-structured interviews, and document analysis. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing and verification. The findings revealed that teachers integrated technological, pedagogical, and content knowledge into lesson planning, classroom instruction, and assessment by utilizing digital learning media, interactive presentations, and online educational resources. This implementation enhanced students' participation in classroom activities, facilitated their understanding of abstract concepts through visual and interactive learning materials, and encouraged more active learning interactions. However, challenges remained, including limited technological infrastructure, uneven digital competencies among teachers, and unstable internet connectivity. Continuous professional development and institutional support are therefore essential to strengthen teachers' TPACK competencies. In conclusion, the implementation of TPACK contributes to improving learning quality and supports the achievement of SDG 4 by promoting inclusive, technology-integrated, and student-centered learning practices in primary education.